Discrete exterior calculus and higher order Whitney forms - Lohi, Jonni (2019)
Partial differential equations describing various phenomena have a natural expression in terms of differential forms. This thesis discusses higher order Whitney forms as approximations for differential forms. We present how they can be used with discrete exterior calculus to discretise and solve partial differential equations formulated with differential forms.